PENGEMBANGAN INTELEGENSI MUSIKAL SISWA MELALUI PEMBELAJARAN MUSIK DI SEKOLAH - Pratik Hari Yuwono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
Every human being has two hemispheres of the brain that is the left brain and right brain. The left hemisphere is used to control mental activities that include mathematical skills, language, logic, analysis, writing, and similar activities, while the right hemisphere includes activity such as imagination, color, music, rhythm / rhythm, dreamy and activities similar. The theory of multiple intelligence trying to combine both the ability of the right and left hemispheres of the brain possessed by humans. So according to this theory people can have the ability / intelligence more than one to run its activities where the ability / intelligence is controlled by the right hemisphere and the left brain. All the people in general to be able to develop its intelligence-intelligence and intelligence diligently to train owned by the company in order to develop according to its potential. To educators and prospective educators in particular to be more selective and careful in identifying intelligence possessed by learners, as each protégé has a different intelligence who all wanted to get a good stimulus or response in order to develop intelligence. Develop musical intelligence has its own benefits and advantages of the development of the child. Keywords: musical intelligence, musical art